Current Insights and Management Strategies for Lower Cervical Arteriovenous Fistulas: A Comprehensive Review - Iampreechakul, Prasert; Wangtanaphat, Korrapakc; Chuntaroj, Songpol; Angsusing, Chonlada; Wattanasen, Yodkhwan; Hangsapruek, Sunisa; Lertbutsayanukul, Punjama; Siriwimonmas, Somkiet (Asian Journal of Neurosurgery, 2025)
Lower cervical arteriovenous fistulas (AVFs) are rare and complex vascular malformations that pose significant clinical challenges due to their location and variable presentation. While upper cervical AVFs have been extensively studied, lower cervical AVFs remain underresearched. This study aims to review the clinical presentations, management strategies, and outcomes of patients with lower cervical AVFs to enhance understanding and improve treatment approaches. We conducted a retrospective analysis of patients with spinal vascular malformations treated at our institute between June 2006 and December 2023, identifying two cases of lower cervical AVFs. Additionally, a systematic literature review was performed following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, including 44 patients with lower cervical AVFs, using databases such as Ovid MEDLINE, PubMed, and Cochrane. Data collected included patient demographics, clinical presentation, fistula type, arterial and venous involvement, treatment modality, and neurological outcomes. Among the 44 patients with lower cervical AVFs, including our two cases, 50% were female, and the mean age was 48.68 years (range: 4–76 years). Clinical presentations varied, with 27.3% experiencing hemorrhage, 18.2% presenting with myelopathy, and 18.2% remaining asymptomatic. Venous drainage patterns played a significant role in symptom severity, with complex perimedullary and retrograde venous drainage contributing to worse outcomes. Treatment included endovascular embolization (40.9%), surgical resection (25%), and combined approaches (18.2%), with good recovery achieved in 54.5% of cases. Lower cervical AVFs present diverse clinical challenges due to their variable presentations and complex vascular anatomy. Early diagnosis and tailored management, including endovascular embolization and surgical resection, are essential for optimizing patient outcomes. Further research is needed to better understand the natural history of asymptomatic AVFs and improve treatment protocols.
Keywords: lower cervical arteriovenous fistulas; spinal dural arteriovenous fistula; epidural arteriovenous fistulas; perimedullary arteriovenous fistulas; radicular arteriovenous fistulas; spinal cord venous infarction